The safe man ebook A ghost story. - Connelly, Michael (2012)
Read the riveting detective story that inspired the Audible dramatization featuring Jack Quaid and Titus Welliver. Like his father before him, Brian Holloway is a safe man. That is, his specialty is opening safes. Every job is a little mystery, and he has yet to encounter a lock he can't break or a box he can't crack. But the day Holloway gets called in to open a rare, antique safe in a famous author's library, his skills open a door that should have remained closed. In this haunting and singular story, previously published anonymously, Michael Connelly proves once again that he is "superb at building suspense.... the reader can never be sure what sudden turns the plot may take" ( Wall Street Journal ). [Word count: 11,662]